Rekayasa Jurnal Teknik Sipil Volume 7 Nomer 2 Desember 2022 - Rekayasa Jurnal Teknik Sipil Volume 7 Nomer 2 Desember 2022 (Rekayasa: Jurnal Teknik Sipil, 2022)
Rekayasa Jurnal Teknik Sipil Volume 7 Nomer 2 Desember 2022